Factors Influencing Consumer Purchase Decisions for Aqua Life Indonesia Products: Analysis of Ecolabel Awareness, Green Marketing Mix, and Brand Image - Shafira, Nabilla; Sarma, Ma'mun; Rahmayani Johan, Irni (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aims to answer two main objectives. The first is to answer the current eco-label, green marketing mix, and brand image of AQUA Life, and the Second is to answer how eco-label awareness, green marketing mix, and brand image influence consumer purchasing decisions. The study was conducted from November to December 2021. The data collected in this study were primary data obtained from a questionnaire survey in Indonesian, which was distributed via the Google Form link using the Ordinal scale. The sampling method (respondents) used is purposive sampling. The data was processed and analyzed using Structural Equation Modeling. The study's results obtained 105 respondents and showed that the eco-label awareness variable did not significantly affect consumer purchasing decisions for AQUA Life products. The green marketing mix and brand image variables positively and significantly impact consumer purchasing decisions for AQUA Life products. A green marketing mix has a significant effect on brand image. Producers and the government must provide more education to consumers to gain more knowledge about the use of environmentally friendly products and their benefits. Keywords: brand image, consumer purchasing decisions, ecolabel awareness, green marketing mix, structural equation modeling